Laparoscopic double-tract reconstruction after total gastrectomy for postoperative duodenal surveillance: Case series. (September 2017) - Otsuka, Ryota; Hayashi, Hideki; Hanari, Naoyuki; Gunji, Hisashi; Hayano, Koichi; Kano, Masayuki; Matsubara, Hisahiro
Abstract: Introduction: When gastric cancer or carcinoid patients have coexisting diseases such as duodenal adenoma, FAP, or Crohn's disease, periodic observation of the duodenum is necessary. Methods: Between August 2013 and April 2015, we performed four consecutive laparoscopic total gastrectomies with double tract reconstruction for duodenal surveillance. Three of the patients were diagnosed with gastric cancer, while the remaining patient was diagnosed with gastric carcinoid. Results: No deaths occurred, and three of the patients showed no early complications. One patient with Crohn's disease developed anastomotic leakage, but it was successfully managed conservatively. On endoscopy three to seven months later, we were able to observe the duodenum via jejunal anastomosis in all of the patients. Discussion: Roux-en-Y reconstruction is one of the options after laparoscopic total gastrectomy. However, given that periodical endoscopic examinations of the duodenum are strongly recommended after surgery, double-tract reconstruction may be preferable in these patients. Conclusion: Although more detailed data are required, double-tract reconstruction may be the best choice for patients requiring total gastrectomy with regular check-up of the duodenum. Highlights: When gastric cancer patients have coexisting duodenal diseases, periodic observation of the duodenum is necessary. Given that postoperative endoscopic examinations of the duodenum are needed after total gastrectomy, double-tract reconstruction may be preferable. This is the first report of total gastrectomy with double-tract reconstruction in gastric cancer patients with FAP. Double-tract reconstruction following total gastrectomy may be technically feasible for duodenal surveillance.